2009
DOI: 10.1159/000211380
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Eosinophilic Pneumonia Successfully Treated with Suplatast Tosilate Alone

Abstract: We report a case of eosinophilic pneumonia that was successfully treated with suplatast tosilate. A 72-year-old woman with hypertension and diabetes, who did not smoke and did not have pets, consulted a physician with the chief complaints of cough, sputum, and slight fever. Chest X-ray films revealed a permeation shadow in the bilateral upper lobes. She visited a hospital because her symptoms did not improve. Pulmonary tuberculosis was suspected because of an elevated inflammatory reaction, and anti-tuberculos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In recent years, a few case reports have demonstrated the successful treatment of CEP with suplatast tosilate due to intolerance of hormone therapy. 14 It has also been reported that monoclonal antibody omalizumab has a significant effect in the treatment of CEP. 15 , 16 , 17 Monoclonal antibody omalizumab is an anti‐IgE antibody used in asthma and other allergic diseases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In recent years, a few case reports have demonstrated the successful treatment of CEP with suplatast tosilate due to intolerance of hormone therapy. 14 It has also been reported that monoclonal antibody omalizumab has a significant effect in the treatment of CEP. 15 , 16 , 17 Monoclonal antibody omalizumab is an anti‐IgE antibody used in asthma and other allergic diseases.…”
Section: Discussionmentioning
confidence: 97%
“…Suplatast tosilate has antiasthmatic, anti‐inflammatory, and antifibrotic activities. In recent years, a few case reports have demonstrated the successful treatment of CEP with suplatast tosilate due to intolerance of hormone therapy 14 . It has also been reported that monoclonal antibody omalizumab has a significant effect in the treatment of CEP 15–17 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there were a few case reports of successful treatment of CEP by suplatast tosilate due to intolerance of hormone therapy [18]. Suplatast tosilate is mainly used to treat asthma and allergic rhinitis, which can reduce IgE synthesis by inhibiting the production of interleukin-4 by T cells.…”
Section: Discussionmentioning
confidence: 99%